Foreign direct investment in Central and Eastern Europe after two decades of EU enlargement - Jaklič, Andreja (Acta Histriae, 2024)
This article examines foreign direct investment (FDI) as an indicator of economic integration, focusing on Central and Eastern Europe (CEE) in the two decades they have been EU members. Although CEE countries have remained on the EU’s periphery and struggled with development gaps, they have attracted substantial FDI, especially in the first decade after accession, fuelling the growth of outward FDI and integration into global value chains. Despite CEE economies like Slovenia and Hungary having seen differences in their use of FDI, such investment and European integration will remain central to the region’s economic development, even amid the ongoing geopolitical tensions.
Keywords: Central and Eastern European countries; economic integration; foreign direct investment; global value chains; Mednarodno gospodarsko povezovanje; Tuje naložbe